Pengaruh Brand Ambassador Chanyeol EXO Terhadap Keputusan Pembelian Produk Nacific Pada Komunitas EXO-L Purwakarta - Putri, Annisa Agustiana; KM, Maman Rosama; adriansah, adriansah (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2022)
This study aims to find out how the influence of EXO’s Chanyeol as a brand ambassador on purchase decision of NACIFIC products in EXO-L Purwakarta community. In this study, quantitative method were used with correlational approach and using purposive sampling technique with the following criteria: (a) members of EXO-L Purwakarta whatsapp group; (b) have/are using NACIFIC products. To determine the number of samples, the slovin formula was used and resulted in a sample number of 80 respondents from a population of 100 people. As for variable X, theory of brand ambassador indicator from Shaz Smilansky and for variable Y, namely purchase decision, theory of purchase decision indicators from Engel is used. Based on the results of the analysis that has been carried out, it can be concluded EXO's Chanyeol as brand ambassador has a significant positive influence on the purchase decision of NACIFIC products in EXO-L Purwakarta community by producing a regression coefficient value of 0.475 and a calculated t value > table t of 3.203 > 1.991